Effect of BMP-2 with Microfracture on Osteochondral Defect in a Rabbits Talus. Issue 4 (16th October 2019) - Dang, Le Hoang Nam; Lee, Kwang-Bok
Category: Ankle, Basic Sciences/Biologics Introduction/Purpose: Microfracture is a technically safe, simple and cost-effective treatment option for osteochondral defect of the talus. However, fibrous tissue and fibrocartilage represent the predominant repairing tissues derived from these procedures and these tissues types do not exhibit the mechanical properties of native hyaline cartilage, long time for cartilage reconstruction and long-term failure results. Bone morphogenetic protein-2 (BMP-2) has been shown to stimulate matrix synthesis and increase in synthesis of cartilage-specific collagen type IIB thereby enhance regeneration of articular cartilage in vitro. The purpose of this study is to evaluate the treatment ability of combining BMP-2 with microfracture on osteochondral defect in rabbit talus. Methods: Full-thickness chondral defects (3 x 3 x 2 mm) was created in the center talus dome. Twenty four male white New Zealand rabbits were divided into four groups of 6 animals into each group dependent on treatment method; Group I (control, no treatment), II (microfracture only), III (10 µL rhBMP-2 treatment), IV (microfracture combine with 10 µL rhBMP-2 treatment). The animals were sacrificed at 2, 4, 6 weeks post operatively. The macroscopic assessment of the repaired tissue was evaluated using the International Cartilage Repair Society (ICRS) Macroscopic Score, which considers the degree of defect repair, the integration to the border zone, and the macroscopic appearance. Subchondral bone regeneration on defect was evaluated by micro-CT scan and the histological findings were scored by using a modified version of the established scoring system for osteochondral repair described by Wakitani, immunohistochemical staining was used for analysis of collagen type I and II. Results: : Excessive bone formation that originated from the subchondral bone region was not observed in any sample. Micro-CT shows higher subchondral bone regeneration on defect in group III, IV than group I, II at 4 and 6 weeks, respectively. According to macroscopic and histological results, group V shows higher quality of cartilage and faster cartilage regeneration compare with another group. In immunohistochemical analysis, group IV shows stronger positive staining for collagen type II in the area of the defect. Conclusion: These findings indicate that the combination BMP-2 with microfracture is effective at accelerating and improving quality of full-thickness cartilage defect repair in a rabbit talus model.